Assessing health risk due to exposure to arsenic in drinking water in Hanam Province, Vietnam - Huy-Tung, B.; Tuyet-Hanh Tran Thi; Hung Nguyen-Viet (2012)
Estimating health risk caused by As exposure in drinking water is important to understand the impact of As contaminated drinking water and to prioritize the interventions. We characterized the As contamination and assessed health risk related to As contaminated water in Duy Tien district, Hanam province using the Australian Environmental Health Risk Assessment Framework. Exposure assessment was conducted by measuring As concentrations in 300 tube-well water samples before and after filtration, estimating water volume consumed for drinking purpose in 150 interviewed households, which gave the daily consumption dose from oral route. Health risk was characterized by comparing the As levels in water with the National technical regulations on drinking water quality, and by comparing the daily consumption dose with the Tolerable Daily Intake (TDI) value set by WHO. Finally, cancer risk of people using As contaminated water source for eating and drinking was estimated using Cancer Slope Factor index and lifetime average daily dose. Results showed that water was heavily contaminated with As. The concentrations in drinking water before filtration were from 8 – 579 ppb (mean 301 ppb). The majority of households designed their sand filters themselves, but filters did not meet the standard for As removal. As daily consumptions of 60% adults were lower than the level of the TDI (1 µg/kg/day). The average cancer risk in adults due to consuming filtered tube-well water for drinking purpose was 23.5 x 10-5. This cancer risk would be 1.2 and 1.5 times higher after five and 10 years drinking filtered water, respectively. Our study showed the high contamination levels of As in tube-well water in Hanam. Improved filtration measures or the replacement of the current drinking water source (i.e. by rain water, clean pipe water...) to prevent health risk for local population are recommended.